Thromboelastography with Platelet Mapping Detects Platelet Dysfunction in Patients with Aneurysmal Subarachnoid Hemorrhage with Rebleeding - He Q; Zhou Y; Liu C; Zhang X; Huang N; Wang F; Liu G; Cheng Y; Xie Z (Neuropsychiatric Disease and Treatment, 2019)
Qiuguang He,1 You Zhou,2 Chang Liu,3 Xiang Zhang,1 Ning Huang,1 Feng Wang,1 Guodong Liu,1 Yuan Cheng,1 Zongyi Xie1 1Department of Neurosurgery, The Second Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 2Department of Critical Care Medicine, The Second Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 3Department of Neurology, The Second Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of ChinaCorrespondence: Zongyi XieDepartment of Neurosurgery, The Second Affiliated Hospital of Chongqing Medical University, Chongqing 400010, People’s Republic of ChinaEmail zyxieneuro2013@yahoo.comBackground: Aneurysmal subarachnoid hemorrhage (aSAH) has high rates of disability and mortality, and aneurysm rebleeding is associated with poor functional outcomes. Thrombelastography with platelet mapping (TEG-PM) measures platelet function; however, it has not yet been researched in aSAH. We aimed to use TEG-PM to detect changes in platelet function in patients with aSAH and the difference in patients with and without rebleeding.Methods: We retrospectively included patients with aSAH who underwent a TEG-PM test on admission. Rebleeding was diagnosed according to clinical and imaging data. TEG-PM data of patients with unruptured intracranial aneurysms (UIA) were also obtained as controls. Univariate and multivariate logistic regression models were performed to investigate the relationship between the platelet function and rebleeding.Results: A total of 245 aSAH patients and 32 UIA patients were included in our study. Compared with controls, patients with aSAH demonstrated higher arachidonic acid (AA) and adenosine diphosphate (ADP) inhibition of platelet function (P<0.05). Among them, 27 patients with Hunt-Hess grade IV or V were classified as the severe SAH group. There was a significant correlation between the severe SAH group and the degree of pathway inhibition (P<0.05). Furthermore, AA (Spearman’s r=0.264, P<0.001) and ADP (Spearman’s r=0.183, P=0.004) inhibition were elevated in Hunt–Hess grade-dependent manners. The AA (Spearman’s r=0.169, P=0.008) and ADP (Spearman’s r=0.233, P<0.001) inhibition were also significantly correlated with Fisher grade. Thirty-five patients (14.3%) suffered rebleeding. Rebleeding was significantly correlated with systolic blood pressure (P=0.011), diastolic blood pressure (P=0.008), Hunt–Hess grade (P=0.034), Fisher grade (P=0.015), AA inhibition (P<0.001), and ADP inhibition (P<0.001). Multivariate logistic regression analysis model revealed that both AA (P=0.037) and ADP inhibition (P=0.008) were independent determinants for rebleeding.Conclusion: TEG-PM may assess platelet dysfunction in patients with aSAH, and the diminished platelet response to ADP and AA may be associated with rebleeding. These findings deserve further investigation.Keywords: aneurysmal subarachnoid hemorrhage, thromboelastography, platelet function, rebleeding